Perceforest : The Prehistory of King Arthur's Britain. - Bryant, Nigel, 1953- (Cambridge, U.K. ; Rochester, NY : D.S. Brewer, 2011)
A highly readable version of this remarkable and largely unexplored work.
Chapters XLIII-XLV -- Chapter XLVI -- Chapters XLVII-XLIX -- Chapter L -- Chapters LI-LII -- Chapters LIII-LIV -- Chapter LV -- Chapter LVI -- Chapter LVII -- Chapters LVIII-LIX -- BOOK FIVE -- Chapters I-II -- Chapter III -- Chapter IV -- Chapter V -- Chapter VI -- Chapter VII -- Chapter VIII -- Chapter IX -- Chapter X -- Chapters XI-XII -- Chapter XIII -- Chapter XIV -- Chapters XV-XVIII -- Chapter XIX -- Chapters XX-XXI -- Chapter XXII -- Chapters XXIII-XXV -- Chapter XXVI -- Chapters XXVII-XXXI -- Chapter XXXII -- Chapter XXXIII -- Chapters XXXIV-XXXVI -- Chapters XXXVII-XXXVIII
Description based upon print version of record.
Includes bibliographical references and index.
Chapter XXXIX
Translated from the Old French.
JSTOR
Keywords: Perceforest -- Translations into English; Arthurian romances; Romances; Cycle d'Arthur.; Roman courtois; romances (medieval narratives); romances (medieval narratives); Romances; Arthurian romances; Romans courtois; Cycles d'Arthur.